FOOD LABELING AND SUSTAINABILITY: IMPACTS OF REGULATORY COMPLIANCE ON MENU PLANNING AND REDUCING FOOD WASTE - Defrein, Talita; Geiza dos Anjos, Andréa; Ottoni Zimmermann, Guilherme; Novais da Silva, Fernando (Revista Gênero e Interdisciplinaridade, 2025)
With the growth of industrial food production and the expansion of the food sector, clear, objective, and safe communication with consumers has become essential. In this context, labeling stands out as the primary source of information, requiring regulations that ensure quality, safety, and standardized presentation. The publication of more precise norms reinforces the need for industries and regulatory bodies to comply with established requirements; however, full adherence to legislation remains a challenge. This study aimed to evaluate the labeling conformity of eight groups of food products marketed in the city of Joinville (SC) based on current Brazilian legislation. Among the 40 labels analyzed, all presented at least one type of nonconformity. Group VII—Sugars and products with energy derived from carbohydrates and fats—showed the highest number of irregularities. The nutrition facts table was the most frequently noncompliant item, both in formatting and nutrient presentation, highlighting the difficulty industries face in fully following regulatory standards. Although legislation provides clear guidelines to facilitate compliance, there is a notable need for regulatory-affairs teams with stronger technical expertise. In addition to promoting transparency and food safety, nutritional labeling is also linked to sustainability and food waste reduction. Brazil’s Law No. 14.016/2020, which regulates the donation of surplus food suitable for human consumption, reflects the importance of public policies aimed at reducing waste. This commitment aligns with the United Nations 2030 Agenda, particularly SDG 12 – Responsible Consumption and Production, which seeks to halve global food waste and foster more sustainable production chains. Thus, labeling serves not only as a regulatory instrument but also as a tool for environmental education and awareness, strengthening the connection between information, health, and sustainability.